Environmental and Social Management System Implementation Handbook : Animal Production - International Finance Corporation (Washington, DC, 2014)
Environmental and social responsibility is becoming more and more important in todayapos;s global economy. There are thousands of environmental and social codes and standards in the world today. The codes and standards define the rules and the objectives. But the challenge is in the implementation. An environmental and social management system (ESMS) helps companies to integrate the rules and objectives into core business operations, through a set of clearly defined, repeatable processes. This Handbook is intended to be a practical guide to help companies in the animal production industry develop and implement an environmental and social management system, which should help to improve overall operations. Some people think that an environmental and social management system must be big, complicated and expensive. But that is not really true. To be effective, a management system needs to be scaled to the nature and size of the company. If a company has existing management systems for quality or health and safety, this Handbook will help to expand them to include environmental and social performance. Sections I and II provide background on environmental and social management systems (ESMS) in the animal production industry. Section III provides step-by-step instructions on how to develop and implement an ESMS. The ESMS Toolkit and Case Studies section offers tools to help you develop and implement the systems described in this Handbook, as well as two case studies in the animal production industry that implemented an ESMS. The Self-Assessment and Improvement Guide offers tools to measure the maturity of an ESMS and to develop a plan for improvement. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.